2023
DOI: 10.3390/e25071085
|View full text |Cite
|
Sign up to set email alerts
|

EnRDeA U-Net Deep Learning of Semantic Segmentation on Intricate Noise Roads

Abstract: Road segmentation is beneficial to build a vision-controllable mission-oriented self-driving bot, e.g., the Self-Driving Sweeping Bot, or SDSB, for working in restricted areas. Using road segmentation, the bot itself and physical facilities may be protected and the sweeping efficiency of the SDSB promoted. However, roads in the real world are generally exposed to intricate noise conditions as a result of changing weather and climate effects; these include sunshine spots, shadowing caused by trees or physical f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…3, on the basis of the basic U-Net architecture, the improved U-Net model introduces the channel attention mechanism and optimizes the convolutional layer and other parts to enhance the model's feature extraction and segmentation performance. The model starts from the input image and first extracts low-level features through two consecutive 3 × 3 convolutional layers (Conv2D-64) [61]. Then, a channel attention mechanism is used to strengthen channel relationships to better capture historic building gene image information of different scales and types in subsequent feature extraction.…”
Section: Improved U-net Model For Integrating a Channel Attention Mec...mentioning
confidence: 99%
“…3, on the basis of the basic U-Net architecture, the improved U-Net model introduces the channel attention mechanism and optimizes the convolutional layer and other parts to enhance the model's feature extraction and segmentation performance. The model starts from the input image and first extracts low-level features through two consecutive 3 × 3 convolutional layers (Conv2D-64) [61]. Then, a channel attention mechanism is used to strengthen channel relationships to better capture historic building gene image information of different scales and types in subsequent feature extraction.…”
Section: Improved U-net Model For Integrating a Channel Attention Mec...mentioning
confidence: 99%
“…In addition, the Adam algorithm has the advantage of changing the optimal learning rate according to the update intensity of each parameter. A study by Xiaodong Yu (2023) [27], similar to this paper, applied the Adam optimizer in PyTorch 1.10.0 to train the network. Initially, the learning rate was set to 1 × 10 −4 and was dynamically tuned in terms of exponential decay, the epoch was set to 120, and batch_size was set to 8.…”
Section: Crack Detection Algorithmsmentioning
confidence: 99%
“…The observation indicated that when the epoch reached a value of 20, the loss then tended to saturate and terminate to prevent overfitting, so that generalization was increased further. When the epoch reached a value of 100, the loss attained a level of 0.04 and tended toward stabilization [27]. Second, the Adam function was used to optimize the U-Net model.…”
Section: Crack Detection Algorithmsmentioning
confidence: 99%
“…Zhang et al [30] employed an enhanced ResNet-50 as the underlying network architecture in their experiments to overcome the limitations of U-Net [31][32][33]. These limitations include suboptimal crack segmentation performance and difficulties in identifying narrow cracks, while also improving inference speed compared to the standard U-Net.…”
Section: Introductionmentioning
confidence: 99%